Perancangan Alat Penyiram Tanaman Otomatis Pada Tanaman Seledri Berbasis Telegram Menggunakan Nodemcu - Romiyadi, Rizar; Adi, Siska Minati; Rozany, Boy Abidin; Fitriani, Ratna (STMIK Banjarbaru, 2024)
Celery plants have many benefits, both as food ingredients such as soup and herbal medicine for various diseases such as fever, flu, digestive disorders, and hypertension. However, celery watering by farmers is still done manually, which often causes suboptimal plant growth due to incorrect water measurements. Changes in soil moisture are also a problem, especially when farmers cannot water regularly. This study uses the Research and Development (R&D) method and produces an automatic sprinkler with a Soil Moisture sensor that detects soil moisture. If the humidity drops below 65%, the water pump will turn on, and if the humidity rises above 75%, the pump will turn off. These settings can be controlled via the Telegram application with the command